THE TEREK COSSACKS’ STRUGGLE AGAINST THE BOLSHEVIKS IN THE SUMMER-AUTUMN OF 1918 THROUGH THE MEMOIRS OF GENERAL G.A. VDOVENKO - Lobanov, Vladimir Borisovic (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines the memoirs of General G.A. Vdovenko to analyze the Terek Cossacks’ struggle against the Bolsheviks during the 1918 Terek Uprising, a pivotal event in the North Caucasus during the Russian Civil War. Utilizing established historical research methodologies, including historicism, objectivity, and systematic analysis, this study investigates the causal relationship between the initial neutrality of the Terek Cossacks in late 1917 and early 1918 and the subsequent Sovietization of the Terek region. The research findings indicate that the Bolsheviks’ anti-Cossack agrarian policies, formalized at the Third Congress of the Working Peoples of the Terek in May 1918, instigated a radical shift in Cossack sentiment, culminating in the Terek Uprising of June-August 1918. This uprising marked the large-scale involvement of the Terek Cossacks in the anti-Bolshevik movement within the Volunteer Army and the Armed Forces of Southern Russia. The theoretical significance of this work lies in its contribution to a more nuanced understanding of the Civil War in the North Caucasus and the specific role of the Terek Cossacks within this conflict. The findings and conclusions presented herein are relevant for educational institutions studying the Soviet period of Russian history, particularly the years 1917-1922.
Keywords: Terek Cossacks; mountaineers; revolution; Civil War; Terek; Dagestan; Karaulov; Denikin; Chermoev; Kotsev